2020
DOI: 10.1021/acsomega.0c03264
|View full text |Cite
|
Sign up to set email alerts
|

Droplet-Based Cytotoxicity Assay: Implementation of Time-Efficient Screening of Antitumor Activity of Natural Killer Cells

Abstract: Natural killer (NK) cells are key players of the innate immune system. Due to their rapid cytotoxicity against infectious pathogens, hematologic malignancies, and solid tumors, NK cells represent solid candidates for cell-based immunotherapy. Despite the progress made in recent years, the heterogeneity in their cytotoxic behavior represents a drawback. With the goal of screening the intrinsic diversity of NK cells, droplet-based microfluidic technology is exploited to develop a single-cell time-efficient cytot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 46 publications
(79 reference statements)
1
21
0
Order By: Relevance
“…Even though these platforms achieved high pairing efficiencies and dynamic monitoring, they failed to exclude paracrine signalling between neighbouring cells and lack high throughput, important factors that need to be considered when studying and understanding functional heterogeneity in immune cells 30 . Furthermore, the droplet-based cytotoxicity platform developed by Sarkar et al utilized a docking array-based system, allowing the visualization of around 4000 droplets and the platform developed by Antona et al utilized spherical traps, allowing the visualization of around 6500 droplets per experiment 20 , 21 . These studies analyzed approximately 100 droplets to study the cellular interaction in between NK cells and target wells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though these platforms achieved high pairing efficiencies and dynamic monitoring, they failed to exclude paracrine signalling between neighbouring cells and lack high throughput, important factors that need to be considered when studying and understanding functional heterogeneity in immune cells 30 . Furthermore, the droplet-based cytotoxicity platform developed by Sarkar et al utilized a docking array-based system, allowing the visualization of around 4000 droplets and the platform developed by Antona et al utilized spherical traps, allowing the visualization of around 6500 droplets per experiment 20 , 21 . These studies analyzed approximately 100 droplets to study the cellular interaction in between NK cells and target wells.…”
Section: Resultsmentioning
confidence: 99%
“…The effector (NK cells) and the target (K562) cells were paired together in 70 pL droplets, allowing them to interact. The study by Antona et al showed that cells in a confined environment, such as droplets, increase the chances of cellular interaction 21 . However, we observed that only around 20% of NK cells were potent killers, while the large majority were not able to induce killing at all during the 10 h of incubation, which is in agreement with the two earlier micro-well based studies by Vanherberghen et al 2 and Gudeval et al 3 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Serial killing by NK-92 cells has been documented before; however, we directed our attention to potential in vivo effects on serial killing. A previous study focused on the development of a droplet-based cytotoxicity assay that utilized a lowest E:T of 1:3 and showed that ~50% of observed NK-92 cells are able to serially kill two or more K562 targets in 12 hours (34). Serial cytotoxicity has also been observed with time-lapse cinematography using genetically modified, IL-2 producing NK92-MI cells.…”
Section: Discussionmentioning
confidence: 99%
“…First, >99% of droplets are empty when these systems are tailored to obtain one cell per droplet unless very specific conditions can be met 4 . Second, it is difficult to precisely quantify droplets maintained in large, open chambers 5 . Third, confining droplets into microwells 6 may aid time-lapse imaging and effective clone selection from a pool, but the propensity of empty droplets will greatly increase workload if all cells of a tumor need to be analyzed to address heterogeneity.…”
Section: Introductionmentioning
confidence: 99%